Disaster-FD: Um detector de falhas para ambientes suscetíveis a desastres - Silva, Abadio de Paulo (2024)
Disaster-FD is a fault detection system for IoT networks in remote environments subject to disasters. Built on top of Impact-FD, Disaster-FD focuses on active monitoring and network reliability assessment, investigating essential elements such as reliability threshold, trust level, and impact factor. The sys-tem presents improvements over its predecessor, with a special focus on real-time monitoring and the accuracy of the estimated time calculation for the next message. The effectiveness of Disaster-FD was demonstrated through experiments on the IoT-LAB platform. The tests included monitoring two distinct regions, allowing for the simulation of real disaster scenarios and the assessment of network reliability in different locations. The federated monitoring capability in Disaster-FD is a crucial component for the fault detector to perform effective monitoring across multiple geographic regions. Additionally, the system monitors the energy consumption of IoT devices, aiming for sustainability and energy efficiency in prolonged disaster scenarios. These technological advancements position Disaster-FD as a promising solution in fault management and disaster response in IoT networks. It is worth noting that the test results obtained with Disaster-FD were superior compared to its predecessor, Impact-FD.